Factors Associated with the Overweight of Primary Students in Public School - ตันติเอกรัตน์ ศศิธร; คุณีพงษ์ อภิชัย (Journal of Preventive Medicine Association of Thailand, 2018)
Overweight in children is a complex public health problem that leads to many health concerns. This observational study was aimed to study overweight behaviorof primary students. The sample consisted of 145 children in level 4-6 elementary students devided in to 2 group normal weight (normal, thinness) and overweight (overweight, obesity). Weight and height of overweight children were analyzed by compared with child growth criteria established by the Ministry of Public Health. The research instruments were the following: general information questionnaire, self-efficacy and social support. Data was analyzed using descriptive statistics and Chi-square. The results showed that the samples were 50.3% female, 49.7% male, aged 9-10 years, 55.2%, followed by 11-13 years old, 44.8%. The nutritional status normal weight was 66.9%, overweight and obesewas 10.3% and 7.6%, respectively. Most of the sample had private business/trade occupations 42.1%. The amount of money received was 10-50 baht per day, 55.2%. This study suggests that self-efficacy social support and obesity prevention behaviors were not significantly associated with overweight. (p>.05) Therefore, in organizing activities to prevent overweight in children need to promote other aspects of the same.